Internal Capital Markets and Diversified Firms: Theory and Practice - Sebastian Gatzer; Daniel Hoang; Martin Ruckes (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyze a unique dataset from a survey of CFOs of diversified firms to examine four areas of diversification and internal capital markets: causes and financing effects of corporate diversification, capital budgeting processes, capital investment methods, and reallocation policies in internal capital markets. CFOs see the main financial benefits of being diversified in lower costs of capital and higher debt capacities. Challenging the usual bottom-up view on capital allocation, firms' capital budgeting processes have typically also a top-down component: while top management relies on financial projections provided by divisions it also uses its own qualitative information. Top management is aware of agency and information problems at the divisional level and organizes the budgeting process to counteract managerial opportunism. Firms acknowledge that capital allocation decisions can frequently lead to a more evenly distributed allocation than pure financial criteria suggest.
Keywords: G31; G32; 330; Corporate Investment; Capital Budgeting; Internal Capital Markets